Silaturrahim as a Solution for Broken Homes: An Analysis of the Perspective of Tafsīr al-Marāghi in the Indonesian Context - Syifaa’ ‘Izzatinnisaa’ Naziihah; Naziihah, Syifaa' 'Izzatinnisaa'; Iqbal, Ipmawan Muhammad; Novitasari, Fajar (Jurnal Semiotika Quran, 2025)
The phenomenon of broken home families resulting from high divorce rates has become a serious social challenge in Indonesia, negatively impacting the emotional stability and development of children. This study aims to analyze the concept of silaturrahim (maintaining kinship ties) as a constructive solution for restoring fractured  family  relationships,  using  the  perspective  of  Tafsīr al-Marāghi  as  the primary lens. Employing a qualitative library research method with a descriptive-analytical and thematic analysis (maudhu'i) approach, this study examines Ahmad Musthafa al-Maraghi's interpretation of key verses such as QS. an-Nisā’ 4: 1, QS. ar-Ra’d 13: 21, 25, and QS. an-Nahl 16: 90. The findings indicate that Tafsīr al-Marāghi, with its socio-literary (adabi ijtima’i) style, positions silaturrahim not merely as a moral recommendation but as a divine command that serves as a foundation for piety, justice, and social stability. Severing kinship ties is viewed as a form of corruption on earth (fasād fī al-arḍ) that is strongly condemned. Its implementation in the Indonesian context proves relevant, where the values of silaturrahim are actualized through various psychosocial approaches such as fostering self-acceptance (ridha), guidance and counseling services, effective communication among family members, and the development of resilience through the process of forgiveness. This study concludes that silaturrahim offers an applicable theological and psychosocial framework for reconstructing relationships within fractured families, while also affirming that maintaining kinship bonds is a spiritual responsibility that is not nullified even when the family structure changes.